Energy conversion efficiency in sugarcane cultivars as a function of production environments in Brazil - de Moraes Barbosa, Alexandrius; Rebes Zilliani, Rafael; Tiritan, Carlos Sérgio; Maia Souza, Gustavo; de Almeida Silva, Marcelo [UNESP] (Elsevier, 2021)
Energy production needs to increase in order to meet population and industrial growth in the coming decades, and clean energy that promotes the reduction of polluting gases in the atmosphere is required. Sugarcane is a crop with great potential for bioenergy production due to its high potential for converting solar energy into biomass. In this context, the questions arise: What is the real efficiency of conversion solar energy into biomass by sugarcane? How can the production environment and genetic diversity influence this process? In this sense, the objective of this work was to evaluate the efficiency of the conversion of solar energy into biomass, as well the available energy per hectare, and the productivity of stalks as a function of the production environment in different cultivars. The experiments were carried out in two production environments in Brazil, Prado Ferreira, Paraná State (Production Environment A) and Presidente Bernardes, São Paulo State (Production Environment C) and with three sugarcane cultivars SP80-3280, RB855156 and RB867515 in two cultivation cycles. This study showed: a) the production environment × genotype interaction causes 75.80% variation in stalk productivity; b) biomass productivity is less affected by water deficit than stalk productivity; c) the energy conversion efficiency (ECE) ranged from 2.80 to 4.54% in plant cane and 2.10–3.87% in ratoon cane cycles. The variation of ECE in the production environments was due to four main factors: greater water availability, soil fertility, air temperature and solar radiation.
Keywords: Bioenergy; Biomass; Production; Saccharum spp.; Soil; Variety management